Convergent evolution of reduced energy demands in extremophile fish - Passrow, Courtney N.; Arias-Rodriguez, Lenin; Tobler, Michael; Rutherford, Suzannah (My University, 2017)
Convergent evolution in organismal function can arise from nonconvergent changes in traits that contribute to that function. Theory predicts that low resource availability and high maintenance costs in extreme environments select for reductions in organismal energy demands, which could be attained through modifications of body size or metabolic rate. We tested for convergence in energy demands and underlying traits by investigating livebearing fish (genus Poecilia) that have repeatedly colonized toxic, hydrogen sulphide-rich springs. We quantified variation in body size and routine metabolism across replicated sulphidic and non-sulphidic populations in nature, modelled total organismal energy demands, and conducted a common-garden experiment to test whether population differences had a genetic basis. Sulphidic populations generally exhibited smaller body sizes and lower routine metabolic rates compared to non-sulphidic populations, which together caused significant reductions in total organismal energy demands in extremophile populations. Although both mechanisms contributed to variation in organismal energy demands, variance partitioning indicated reductions of body size overall had a greater effect than reductions of routine metabolism. Finally, population differences in routine metabolism documented in natural populations were maintained in common-garden reared individuals, indicating evolved differences. In combination with other studies, these results suggest that reductions in energy demands may represent a common theme in adaptation to physiochemical stressors. Selection for reduced energy demand may particularly affect body size, which has implications for life history evolution in extreme environments.
Citation: Passow, C. N., Arias-Rodriguez, L., & Tobler, M. (2017). Convergent evolution of reduced energy demands in extremophile fish. PLOS ONE, 12(10), e0186935. https://doi.org/10.1371/journal.pone.0186935
Keywords: Physiological parameters; Sulfides; Bioenergetics; Fish physiology; Convergent evolution; Oxygen metabolism